INTERNALISASI NILAI-NILAI AKHLAQUL KARIMAH DALAM KITAB HILYATU THALIB AL-’ILMI: ANALISIS PERSPEKTIF FILSAFAT PENDIDKAN ISLAM - Abdurrahman; Samsuddin, Samsuddin; Balkis Nur Azizah (Prodi PAI Fakultas Tarbiyah IAI Sunan Giri Trenggalek, 2026)
This study addresses the problem of how the values of akhlaqul karimah (noble character) contained in Bakr bin ‘Abdullah Abu Zaid’s Ḥilyatu Ṭālib al-‘Ilmi can be internalized within the framework of Islamic philosophy of education. The significance of this topic lies in the urgent need to strengthen character education in Islamic institutions in the digital era, where the erosion of moral values is increasingly evident. The objective of the research is to examine the integration of Ḥilyatu Ṭālib al-‘Ilmi’s values with the fundamental concepts of Islamic philosophy of education, offering both theoretical enrichment and practical guidance for contemporary Islamic education. This study employs a qualitative library research approach, analyzing primary sources (the book itself and classical references) and secondary literature through philosophical-hermeneutical analysis. The findings reveal that the book emphasizes key virtues such as sincerity, humility, perseverance, discipline, respect for teachers, and intellectual selectivity. These align with the ontological view of humans as rational and moral beings, the epistemological principle that knowledge is acquired through both revelation and disciplined inquiry, and the axiological aim of forming socially responsible and ethically upright individuals. The study concludes that internalizing Abu Zaid’s adab framework provides a timeless model for Islamic character education. Theoretically, it enriches the discourse on Islamic educational philosophy by bridging classical wisdom with contemporary challenges; practically, it offers actionable guidance for educators, students, and institutions in nurturing morally grounded and intellectually robust learners.